AN ESTIMATION OF PRACTICAL FUNCTIONING FOR CONTROL SYSTEM IN PELLETIZING PROCESS OF CHARGE MATERIALS IN DRUM PELLETIZERS ON BASE OF RECOGNITION METHOD - Pazyuk , Mikhail; Ovchinnikova , Irene; Rengevich , Oleg; Mnykh , Anton; Minyajlo , Natalia (Scientific Journal "Metallurgy", 2020)
The use of method of recognizing optimization in the algorithm of control the top level of control system allows to increase the quantity of informative channels as far as perfection of facilities of measuring and control of parameters of process. The estimation of the practical functioning of offered control system by the pelletizing process of charge materials in drum pelletizers is carried out. The main task of the system of automatic control (САC) the process of pillet sinter of charge is a receipt of maximally possible quantity of standard faction for the terms of current grain-size distribution of charge which enters pelletizer. Such task can be decided by the operative adjusting of quantity of moistening liquid, and also parameters of work of pelletizer - his rate of rotation and angle of slope. Exactness of method of recognizable optimization is determined by the step of surplus of parameters which influence on a process. Thus than less is its value, the more so the real technological situation is adequately represented in the logical-predicative model of object. In the case of the use of algorithm of identification optimization in САC by the process of sintering exactness of determination of size of optimal control will be determined by the error of devices which measure grain-size distribu- «МЕТАЛУРГІЯ».Випуск 1 (41), 2019 15 tion of materials of charge., there is a task of search of error of measuring of grain-size distribution of materials of charge, which, from one side, suits exactness of process of pellet sinter control, and, on the other hand, physically realized as a concrete measuring device. During the use of method of identification optimization in control system by the process of sintering of charge materials all volume of factor space, where the investigated object (pelletizer) functions, give as a logical sum of elementary subareas. Application of the worked out system for process of sintering of materials of charge control in a drum pelletizer allows to reduce the quantity of faction - 3 mm in materials of charge on 5,2 %. For process of sintering of materials of charge control on conditions of sintering machine № 1 the "Metallurgical combine of "Zaporozhstal" can be used any microcomputer with the volume of memory not less than 220 Kb and by a clock rate not below, than 5.0 MHz.